Do Cross-Language Script Differences Enable Bilinguals to Function Selectively When Speaking in One Language Alone? - Hoshino, Noriko; Beatty-Martínez, Anne L.; Navarro-Torres, Christian A.; Kroll, Judith F. (Frontiers in Communication, 2021)
The present study examined the role of script in bilingual speech planning by comparing the performance of same and different-script bilinguals. Spanish-English bilinguals (Experiment 1) and Japanese-English bilinguals (Experiment 2) performed a picture-word interference task in which they were asked to name a picture of an object in English, their second language, while ignoring a visual distractor word in Spanish or Japanese, their first language. Results replicated the general pattern seen in previous bilingual picture-word interference studies for the same-script, Spanish-English bilinguals but not for the different-script, Japanese-English bilinguals. Both groups showed translation facilitation, whereas only Spanish-English bilinguals demonstrated semantic interference, phonological facilitation, and phono-translation facilitation. These results suggest that when the script of the language not in use is present in the task, bilinguals appear to exploit the perceptual difference as a language cue to direct lexical access to the intended language earlier in the process of speech planning.